The Effect of ROA, BOPO, and Interest Rate on Profit Sharing Rate of Mudharabah Deposit at BPRS in Indonesia during 2015-2019 - Aulia, Fena Ulfa; Saputri, Diana Eka (JIFA (Journal of Islamic Finance and Accounting), 2021)
The purpose of this study was to determine the effect of Return On Assets, BOPO, and Interest Rates on the Mudharabah Deposit Profit Sharing Rate at BPRS in Indonesia. This research is a type of explanatory research. The object of this research is BPRS in Indonesia according to the results of the yearly financial reports for 2015-2019. The sampling technique used was simple random sampling technique, and there were 8 BPRS in Indonesia used as samples. The type of data used in this study is quantitative data. The data source in this research is secondary data source. The method used in this study is the Classical Assumption Test and Hypothesis Test. The data collection technique is documentary from the official website of the Financial Services Authority (OJK) and the official website of each BPRS in Indonesia as a complement. The results of the study explain that ROA has no effect on the profit sharing rate of mudharabah deposits at BPRS in Indonesia for the 2015-2019 period with a significance value of 0.274. BOPO has a positive and significant effect on the profit sharing rate of mudharabah deposits at BPRS in Indonesia for the 2015-2019 period with a significance value of 0.010. Interest rates have no effect on the profit sharing rate of mudharabah deposits at BPRS in Indonesia for the 2015-2019 period with a significance value of 0.288. As well as Return On Asset, BOPO, and Interest Rates simultaneously have a significant effect on the Profit Sharing Rate of Mudharabah Deposits at BPRS in Indonesia for the 2015-2019 Period with a significance value of 0.015.